THE IMPROVED PERFORMANCE OF EDITORS IN FINISHING DRAFTS FOR PUBLICATION - Djatmika Djatmika; Riyadi Santosa; Sri Marmanto; Tri Wiratno; Agus Hari Wibowo (Universitas Sebelas Maret, 2021)
Improvement of editors in performing their jobs. Training on effective language exploitation was conducted to editors of publishers in Klaten Regency. Drafts representing their job before and after the training were colleted to be compared on their language performance in improving the texts. The results show that in general the editors have better performance in finishing the drafts for publication. They are more sensitive in identifying grammar mistakes as well as lexical inappropriateness, so that the texts are more effectively revised and improved.